2020
DOI: 10.1103/physrevresearch.2.033167
|View full text |Cite
|
Sign up to set email alerts
|

Work-distribution quantumness and irreversibility when crossing a quantum phase transition in finite time

Abstract: The thermodynamic behavior of out-of-equilibrium quantum systems in finite-time dynamics encompasses the description of energy fluctuations, which dictates a series of the system's physical properties. In addition, strong interactions in many-body systems strikingly affect the energy-fluctuation statistics along a nonequilibrium dynamics. By driving transient currents to oppose the precursor to the metal-Mott-insulator transition in a diversity of dynamical regimes, we show how increasing many-body interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…We first demonstrate that the entropy of the controlled work distribution admits a scaling in line with the predictions of the Kibble-Zurek mechanism [25,26]. This establishes that the controlled evolution provides a versatile means to study generic nonequilibrium dynamics and complements recent studies on the thermodynamics of traversing a quantum phase transition [27][28][29][30][31][32]. As a second application, we propose to use H W as a proxy for the complexity of the control by assessing the work distribution arising from different implementations of counterdiabatic driving for many-body systems.…”
supporting
confidence: 69%
“…We first demonstrate that the entropy of the controlled work distribution admits a scaling in line with the predictions of the Kibble-Zurek mechanism [25,26]. This establishes that the controlled evolution provides a versatile means to study generic nonequilibrium dynamics and complements recent studies on the thermodynamics of traversing a quantum phase transition [27][28][29][30][31][32]. As a second application, we propose to use H W as a proxy for the complexity of the control by assessing the work distribution arising from different implementations of counterdiabatic driving for many-body systems.…”
supporting
confidence: 69%
“…The work distribution for a quantum many-body system is complex. Hence, one usually studies the moments or cumulants of work, such as the mean and variance, in analyzing the work statistics of quantum systems [59][60][61][65][66][67][68][69]. Although the work moments or cumulants can capture several features of nonequilibrium thermodynamics in a variety of many-body systems, they cannot reveal the full information included in the work distribution.…”
Section: Entropy Of the Work Distributionmentioning
confidence: 99%
“…Furthermore, the intersection between quantum information theory and condensed matter physics has been a subject of interest in fermionic models. In particular, it has been shown that entanglement plays a role in the identification of the phases of matter present in the Hubbard model [54][55][56][57][58][59][60] . At the experimental level, quantum simulation of the Hubbard model using ultra cold atoms in optical lattices have been successful in observing and validating the theoretical results of strongly correlated Fermi gases 61 .…”
Section: The Model and The Teleportation Protocolmentioning
confidence: 99%